The cohesin ring concatenates sister DNA molecules. - Haering, C; Farcas, A; Arumugam, P; Metson, J; Nasmyth, K (2008)
Sister chromatid cohesion, which is essential for mitosis, is mediated by a multi-subunit protein complex called cohesin. Cohesin's Scc1, Smc1 and Smc3 subunits form a tripartite ring structure, and it has been proposed that cohesin holds sister DNA molecules together by trapping them inside its ring. To test this, we used site-specific crosslinking to create chemical connections at the three interfaces between the three constituent polypeptides of the ring, thereby creating covalently closed cohesin rings. As predicted by the ring entrapment model, this procedure produced dimeric DNA-cohesin structures that are resistant to protein denaturation. We conclude that cohesin rings concatenate individual sister minichromosome DNA molecules.